Determinants of adoption of multiple sustainable agricultural practices among smallholder farmers in Nigeria - Oyetunde-Usman, Zainab; Olagunju, Kehinde Oluseyi; Ogunpaimo, Oyinlola Rafiat (International Soil and Water Conservation Research, 2021)
Despite the important roles of Sustainable Agricultural Practices (SAPs) in improving productivity, welfare, and food security of farming households, the adoption rates of SAPs have been perceived to be generally low, especially in developing countries. Using cross-sectional data collected from the 2015 Nigeria General Household Survey, this study examines the factors influencing the adoption of multiple SAPs, while also considering the drivers of the intensity of adoption of these practices. The methods of data analysis are based on the Multivariate probit and the Ordered probit models. The SAPs considered include improved seeds, inorganic fertilizer, mixed-cropping techniques, and organic manure. The empirical results show that farmers’ adoption of different SAPs and their intensity of use depend significantly on factors such as the age of household head, gender, education, household size, access to extension services, and household wealth status. Our findings imply that policymakers and agricultural development agencies should seek to maintain or increase household asset bases, and encourage both formal and informal training programme among farming households to facilitate the adoption of SAPs.